Identification and Sensitivity of Vaginal and Probiotic Lactobacillus species to Urinary Antibiotics - Singhal, Lipika; Gupta, Varsha; Gupta, Menal; Goel, Poonam; Chander, Jagdish (Journal of Laboratory Physicians, 2020)
Objectives Healthy vaginal microbiota is mainly dominated by Lactobacillus species namely L. crispatus, L. gasseri, L. jensenii, and L. iners. Lactobacilli are thought to play an important role in the prevention of urogenital infections, and Lactobacillus probiotics to restore and/or maintain vaginal health has been advocated. These can interfere with the adherence, growth, and colonization by uropathogenic bacteria, thus reducing the risk of urinary tract infection (UTI). This study aims to isolate and evaluate the susceptibility of healthy vaginal and probiotic Lactobacillus spp. to urinary antibiotics.Materials and methods A total of 50 premenopausal, nonmenstruating women with no symptoms of vaginal infection or UTI or antimicrobial use in the past 2 weeks were enrolled. Two high vaginal swabs were collected for Nugent’s scoring and anaerobic culture. Colonies yielding gram-positive rods were confirmed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Lactobacillus strains in a vaginal probiotic tablet were also isolated, and the sensitivity of both sets to urinary antibiotics was determined.Results A total of 29 Lactobacillus spp. were isolated, including L. crispatus (15), L. gasseri (5), L. vaginalis (4), L. paracasei (2), L. curvatus (1), L. fermentum (1), and L. paraplantarum (1). All strains were susceptible to nitrofurantoin and resistant to norfloxacin, gentamicin, and cotrimoxazole (except L. paracasei). The probiotic strains were pan-sensitive.Conclusions Prophylactic antibiotics are capable of eliminating the normal vaginal inhabitants, which may increase the probability of UTI. The administration of vaginal probiotics as an alternate or multidrug therapy can restore vaginal microbiota and help prevent recurrent UTI.
Keywords: Lactobacillus; probiotics; UTI; MALDI-TOF